Intervention research on cultivating psychological resilience in adolescent athletes: an empirical analysis based on mindfulness training - Wang, S.; Liu, J. (Frontiers in Psychology, 2025)
Introduction: Psychological resilience is crucial for adolescent athletes facing competitive pressures, yet effective interventions remain understudied. This study examined the associations between mindfulness training and psychological resilience development in adolescent athletes.